Microwave annealing method for reinforcing and toughening Ti3C2Tx film
The treatment of titanium carbide films through microwave annealing method solves the mechanical properties problems caused by spontaneous stacking of titanium carbide nanosheets, and achieves rapid and low-cost tough film preparation, overcoming the shortcomings of traditional heat treatment time and energy consumption.
Patent Information
- Application Number
- CN202411409375.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The existing heat treatment methods are prone to spontaneous stacking of titanium carbide (Ti3C2Tx) nanosheets, resulting in defects and stress concentration, reducing the overall mechanical properties of the material, and consuming time, energy consumption, and difficult to control the degree of oxidation.
Using microwave annealing method, titanium carbide suspension was obtained through physical and chemical reaction treatment, vacuum-assisted filtration and drying to obtain Ti3C2Tx film, and microwave annealing was performed in the microwave reaction chamber, using inert protection gas and adjusting microwave loading power, controlling the annealing process to obtain low Defect density, dense and strong Ti3C2Tx film.
It achieves rapid and low-defect density and high-oriented titanium carbide films with low defect density are achieved, which shortens the annealing time, reduces the thermal stress of the material, maintains a high-entropy structure, and improves the overall performance and production efficiency of the material.
Smart Images

Figure CN119240700A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of post-processing of two-dimensional transition metal nanomaterials, and specifically relates to a method for treating Ti3C2T x Microwave annealing method for strengthening and toughening thin films. Background Art
[0002] Titanium carbide (Ti3C2T x ) is a new type of two-dimensional material, whose chemical formula is composed of titanium (Ti), carbon (C) and surface functional groups (T x ) composition. x It has a graphene-like layered structure in which titanium carbide layers and functionalized group layers are stacked alternately. x It has good electrical conductivity, which makes it have potential applications in electronic devices, batteries, capacitors and other fields. x The functional groups on the surface make it highly chemically active and can react chemically with other substances, such as catalysis and adsorption. x Because of its advantages such as high electrical conductivity, high thermal conductivity, low thermal expansion ratio, surface adjustability, strong hydrophilicity, strong magnetism, and high electrochemical activity, it is highly favored in the fields of electrochemical energy storage, sensors, catalysis, biomedicine, composite materials, etc.
[0003] Compared with graphene, Ti3C2T x With higher bending stiffness, Ti3C2T x The monolayer shows a high Young's modulus value (333 ± 30 GPa), but due to the titanium carbide (Ti3C2T x )Nanosheets tend to stack spontaneously, resulting in defects and stress concentration, which limits their deformation and energy dissipation. This uneven stress distribution actually reduces the overall mechanical properties of the material.
[0004] To improve titanium carbide (Ti3C2T x ) nanosheets tend to spontaneously stack, which can be solved by optimizing the preparation process (such as wet spinning), building composite materials (synergistic effects with different nanofillers), and heat treatment (constant temperature annealing). x ) can reduce its surface defects, enhance toughness and improve its performance. It is an economical and efficient method. However, the existing heat treatment methods have the disadvantages of being time-consuming, energy-intensive, and difficult to control the degree of oxidation. Therefore, it is very necessary to develop a new method that can be used for Ti3C2T x Microwave annealing method for strengthening and toughening thin films. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a method for Ti3C2T x Microwave annealing method for thin film reinforcement and toughening, using Ti3C2T x The electromagnetic response performance can be quickly obtained by microwave heat treatment to obtain strong Ti3C2T x Thin film, compared with traditional annealing methods, microwave annealing saves more power consumption.
[0006] In order to achieve the above objectives, one of the technical solutions of the present invention is: a method for Ti3C2T x The microwave annealing method for strengthening and toughening a thin film comprises the following steps:
[0007] (1) Titanium carbide aluminum (Ti3AlC2) is treated by physical and chemical reaction to obtain a titanium carbide suspension, which is then vacuum-assisted filtered and dried to obtain Ti3C2T x film;
[0008] (2) The Ti3C2T prepared in step (1) x The film sample is placed in a microwave reaction chamber;
[0009] (3) introducing an inert protective gas into the microwave reaction chamber and exhausting the gas in the reaction chamber until all the air in the chamber is exhausted;
[0010] (4) Adjust the microwave loading power to perform microwave annealing on the titanium carbide film, control the total duration of microwave loading power and the power loading period and power stop period in each cycle, so as to obtain a Ti3C2T film with low defect density, denseness, and toughness. x film.
[0011] In a preferred embodiment of the present invention, the physical and chemical reaction in step (1) is specifically to selectively etch with a strong acid, intercalate with an intercalating agent, and peel with physical effects such as ultrasound and centrifugation to finally obtain a suspension of titanium carbide.
[0012] Further preferably, the strong acid is hydrofluoric acid solution or hydrofluoric acid obtained by in-situ reaction of concentrated hydrochloric acid and a fluoride-containing salt, and the intercalant includes at least one of water, ethanol, dimethyl sulfoxide, polymer molecules, and alkali metal-containing ionic salts.
[0013] More preferably, the polymer molecule is polyvinyl alcohol.
[0014] In a preferred embodiment of the present invention, the vacuum-assisted filtration and drying in step (1) is to filter and separate Ti3C2T by using vacuum negative pressure and a water filter membrane. x The film is assisted dried at a temperature not exceeding 60°C.
[0015] In a preferred embodiment of the present invention, the inert protective gas in step (3) comprises at least one of helium, argon and nitrogen.
[0016] In a preferred embodiment of the present invention, the microwave loading power in step (4) is 400-1400W.
[0017] In a preferred embodiment of the present invention, the total time of microwave power loading in step (4) is ≤4s, the power loading period is ≤2s, and the power stopping period is 1-2s.
[0018] In order to achieve the above objectives, the second technical solution of the present invention is: a method for Ti3C2T x Reinforced and toughened Ti3C2T3 films prepared by microwave annealing x film.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The microwave-heated annealing device of the present invention has the characteristics of rapid heating and efficient energy transmission, which can greatly shorten the time required for the annealing process, improve production efficiency, and reduce the generation of temperature gradients and thermal stress, which is conducive to maintaining the overall performance of the material;
[0021] 2. The present invention provides a method for preparing titanium carbide (Ti3C2T x ) film strengthening and toughening method, can obtain low defect density, high orientation titanium carbide (Ti3C2T x ) film; Microwave flash heating helps promote the x The nanosheets are effectively densified without completely melting the material, thereby maintaining its high entropy structure, and microwave annealing is inexpensive, reducing the titanium carbide (Ti3C2T x )The annealing cost of the film is reduced, which is conducive to large-scale quantitative production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The Ti3C2T prepared in Example 1 x Cross-sectional SEM images of the film before and after annealing, (a) before annealing, (b) after annealing. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is described in more detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0024] A kind of material that can be used for Ti3C2T xThe microwave annealing method for strengthening and toughening a thin film comprises the following steps:
[0025] (1) Titanium carbide aluminum (Ti3AlC2) is treated by physical and chemical reaction to obtain a titanium carbide suspension, which is then vacuum-assisted filtered and dried to obtain Ti3C2T x film;
[0026] (2) The Ti3C2T prepared in step (1) x The film sample is placed in a microwave reaction chamber;
[0027] (3) introducing an inert protective gas into the microwave reaction chamber and exhausting the gas in the reaction chamber until all the air in the chamber is exhausted;
[0028] (4) Adjust the microwave loading power to perform microwave annealing on the titanium carbide film, control the total duration of microwave loading power and the power loading period and power stop period in each cycle, so as to obtain a Ti3C2T film with low defect density, denseness, and toughness. x film.
[0029] The physical and chemical reaction in step (1) is specifically to use strong acid for selective etching, use intercalation agent for intercalation, use ultrasound, centrifugation and other physical effects for stripping, and finally obtain a titanium carbide suspension.
[0030] The strong acid includes at least one of concentrated hydrochloric acid, fluorine-containing salt and hydrofluoric acid, and the intercalant includes at least one of water, ethanol, dimethyl sulfoxide, polymer molecules and ion salts containing alkali metals.
[0031] The polymer molecule is polyvinyl alcohol.
[0032] The vacuum-assisted filtration and drying in step (1) is to filter and separate Ti3C2T x The film is assisted dried at a temperature not exceeding 60°C.
[0033] The inert protective gas in step (3) includes at least one of helium, argon and nitrogen.
[0034] The microwave loading power in step (4) is 400-1400W.
[0035] The total time of microwave power loading in step (4) is ≤4s, the power loading period is ≤2s, and the power stopping period is 1-2s.
[0036] A kind of material that can be used for Ti3C2T x Strong and tough Ti3C2T prepared by microwave annealing method x film.
[0037] Example 1
[0038] A kind of material that can be used for Ti3C2T x The microwave annealing method for film reinforcement and toughening comprises the following steps: selecting 2g of titanium aluminum carbide with a mesh size of 400, synthesizing hydrofluoric acid (HF) in situ using 2g of lithium fluoride (LiF) and 40mL of concentrated hydrochloric acid (HCl, with a concentration of 9M), stirring at 35°C for 24h to selectively etch the aluminum (Al) layer, and after the etching process is completed, repeatedly washing the precipitate in the solution with deionized water, and then centrifuging at 3500rpm for 10min until the pH is ≥6. Using ethanol as an intercalation agent, ice bath ultrasonication at 500W power for 1h and then centrifuging at 10000rpm for 10min to obtain a black precipitate at the bottom of the centrifuge tube. After that, the precipitate is carefully redispersed in deionized water, ice bath ultrasonication at 500W power for 20min, and then centrifuged at 3500rpm for 10min to obtain the desired titanium carbide (Ti3C2T x ) suspension; 100mL Ti3C2T x The suspension was filtered by vacuum assisted filtration to obtain the corresponding Ti3C2T x The thin film was placed in a semicircular boat crucible, and the sample to be processed was placed in a microwave reaction chamber; argon was introduced into the reaction chamber, and the air in the reaction chamber was exhausted at the same time until the air in the process chamber was completely exhausted; the microwave loading power was adjusted to 800W, microwaves were applied and plasma spark discharge was observed in the reactor, and then the microwaves were turned off for 2s, and the samples were taken out after waiting for 1s to obtain a strong Ti3C2T x film.
[0039] For the above Ti3C2T x The cross section of the film was observed by SEM scanning before and after annealing. The results are shown in the attached figure. Figure 1 As shown, the Ti3C2T after microwave annealing x Film cross section, compared with unannealed Ti3C2T x The film is denser and neater.
[0040] Example 2
[0041] A kind of material that can be used for Ti3C2T xThe microwave annealing method for film reinforcement and toughening comprises the following steps: selecting 2g of titanium aluminum carbide with a mesh size of 400, using hydrofluoric acid (HF) synthesized in situ by 2g of lithium fluoride (LiF) and 40mL of concentrated hydrochloric acid (HCl, 9M), stirring at 35°C for 24h to selectively etch the aluminum (Al) layer, and after the etching process, repeatedly washing the precipitate in the solution with deionized water, centrifuging at 3500rpm for 10min until the pH is ≥6. Using ethanol as an intercalation agent, ice bath ultrasonication at 500W power for 1h and then centrifuging at 10000rpm for 10min to obtain a black precipitate at the bottom of the centrifuge tube. After that, the precipitate is carefully redispersed in deionized water, ice bath ultrasonication at 500W power for 20min, and then centrifuged at 3500rpm for 10min to obtain the desired titanium carbide (Ti3C2T x ) suspension; 100mL Ti3C2T x The suspension was filtered by vacuum assisted filtration to obtain the corresponding Ti3C2T x The thin film was placed in a semicircular boat crucible, and the sample to be processed was placed in a microwave reaction chamber; argon was introduced into the reaction chamber, and the air in the reaction chamber was exhausted at the same time until the air in the process chamber was completely exhausted; the microwave loading power was adjusted to 400W, microwaves were applied and plasma spark discharge was observed in the reactor, and then the microwaves were turned off for 2s, and the samples were taken out after waiting for 1s to obtain a strong Ti3C2T x film.
[0042] Example 3
[0043] A kind of material that can be used for Ti3C2T x The microwave annealing method for film reinforcement and toughening comprises the following steps: selecting 2g of titanium aluminum carbide with a mesh size of 400, using hydrofluoric acid (HF) synthesized in situ by 2g of lithium fluoride (LiF) and 40mL of concentrated hydrochloric acid (HCl, 9M), stirring at 35°C for 24h to selectively etch the aluminum (Al) layer, and after the etching process, repeatedly washing the precipitate in the solution with deionized water, centrifuging at 3500rpm for 10min until the pH is ≥6. Using ethanol as an intercalation agent, ice bath ultrasonication at 500W power for 1h and then centrifuging at 10000rpm for 10min to obtain a black precipitate at the bottom of the centrifuge tube. After that, the precipitate is carefully redispersed in deionized water, ice bath ultrasonication at 500W power for 20min, and then centrifuged at 3500rpm for 10min to obtain the desired titanium carbide (Ti3C2T x ) suspension; 100mL Ti3C2T x The suspension was filtered by vacuum assisted filtration to obtain the corresponding Ti3C2T xThe thin film was placed in a semicircular boat crucible, and the sample to be processed was placed in a microwave reaction chamber; argon was introduced into the reaction chamber, and the air in the reaction chamber was exhausted at the same time until the air in the process chamber was completely exhausted; the microwave loading power was adjusted to 1400W, microwaves were applied and plasma spark discharge was observed in the reactor, and then the microwaves were turned off for 2s, and the samples were taken out after waiting for 1s to obtain a strong Ti3C2T x film.
[0044] Example 4
[0045] A kind of material that can be used for Ti3C2T x The microwave annealing method for film reinforcement and toughening comprises the following steps: selecting 2g of titanium aluminum carbide with a mesh size of 400, using hydrofluoric acid (HF) synthesized in situ by 2g of lithium fluoride (LiF) and 40mL of concentrated hydrochloric acid (HCl, 9M), stirring at 35°C for 24h to selectively etch the aluminum (Al) layer, and after the etching process, repeatedly washing the precipitate in the solution with deionized water, centrifuging at 3500rpm for 10min until the pH is ≥6. Using ethanol as an intercalation agent, ice bath ultrasonication at 500W power for 1h and then centrifuging at 10000rpm for 10min to obtain a black precipitate at the bottom of the centrifuge tube. After that, the precipitate is carefully redispersed in deionized water, ice bath ultrasonication at 500W power for 20min, and then centrifuged at 3500rpm for 10min to obtain the desired titanium carbide (Ti3C2T x ) suspension; 100mL Ti3C2T x The suspension was filtered by vacuum assisted filtration to obtain the corresponding Ti3C2T x The thin film was placed in a semicircular boat crucible, and the sample to be processed was placed in a microwave reaction chamber; argon gas was introduced into the reaction chamber, and the air in the reaction chamber was exhausted at the same time until the air in the process chamber was completely exhausted; the microwave loading power was adjusted to 800W, microwaves were applied and plasma spark discharge was observed in the reactor, and then the microwaves were turned off for 1 second, and the samples were taken out after waiting for 1 second to obtain a strong Ti3C2T x film.
[0046] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for Ti3C2T x The microwave annealing method for strengthening and toughening a thin film is characterized in that: The following steps are involved: (1) Ti3AlC2 is treated by physical and chemical reaction to obtain a titanium carbide suspension, which is then vacuum-assisted filtered and dried to obtain Ti3C2T x film; (2) The Ti3C2T prepared in step (1) x The film sample is placed in a microwave reaction chamber; (3) introducing an inert protective gas into the microwave reaction chamber and exhausting the gas in the reaction chamber until all the air in the chamber is exhausted; (4) Adjust the microwave loading power to perform microwave annealing on the titanium carbide film, control the total duration of microwave loading power and the power loading period and power stop period in each cycle, so as to obtain a Ti3C2T film with low defect density, denseness, and toughness. x film.
2. The method for Ti3C2T as claimed in claim 1 x The microwave annealing method for strengthening and toughening a thin film is characterized in that: The physical and chemical reaction in step (1) is specifically to use strong acid for selective etching, use intercalation agent for intercalation, use ultrasound and centrifugation for stripping, and finally obtain a titanium carbide suspension.
3. The method for Ti3C2T as claimed in claim 2 x The microwave annealing method for strengthening and toughening a thin film is characterized in that: The strong acid is hydrofluoric acid solution or hydrofluoric acid obtained by in-situ reaction of concentrated hydrochloric acid and a fluoride-containing salt.
4. The method for Ti3C2T as claimed in claim 2 x The microwave annealing method for strengthening and toughening a thin film is characterized in that: The intercalant comprises at least one of water, ethanol, dimethyl sulfoxide, polymer molecules, and ion salts containing alkali metals.
5. The method for Ti3C2T as claimed in claim 4 x The microwave annealing method for strengthening and toughening a thin film is characterized in that: The polymer molecule is polyvinyl alcohol.
6. The method for Ti3C2T as claimed in claim 1 x The microwave annealing method for strengthening and toughening a thin film is characterized in that: The vacuum-assisted filtration and drying in step (1) is to filter and separate Ti3C2T x The film is assisted dried at a temperature not exceeding 60°C.
7. The method for Ti3C2T as claimed in claim 1 x The microwave annealing method for strengthening and toughening a thin film is characterized in that: The inert protective gas in step (3) includes at least one of helium, argon and nitrogen.
8. The method for Ti3C2T as claimed in claim 1 x The microwave annealing method for strengthening and toughening a thin film is characterized in that: The microwave loading power in step (4) is 400-1400W.
9. The method for Ti3C2T as claimed in claim 1 x The microwave annealing method for strengthening and toughening a thin film is characterized in that: The total time of microwave power loading in step (4) is ≤4s, the power loading period is ≤2s, and the power stopping period is 1-2s.
10. A method for Ti3C2T as claimed in any one of claims 1 to 7 x Strong and tough Ti3C2T prepared by microwave annealing method x film.
Citation Information
Patent Citations
Method for regulating surface functional group of Ti3C2 film
CN110105087A
High-toughness Mxene composite electromagnetic shielding film as well as preparation method and application thereof
CN114222493A
Preparation method of MXene nanosheet with rich intralaminar mesopores
CN114715892A
Method and apparatus for selectively annealing heterostructures using microwave
US5707466A
